Evidence of Declining Mortality Trends for Hypertrophic Cardiomyopathy in the United States and the Impact of the COVID‐19 Pandemic - Ahmed Sayed; Barry J. Maron; Ethan J. Rowin; Martin S. Maron (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Dedicated hypertrophic cardiomyopathy (HCM) center cohorts have reported reductions in HCM‐related deaths, likely due to the introduction of contemporary treatments. Similar declining HCM mortality rates are reported in the general US population over 2 decades (1999–2019), but the impact of the COVID‐19 pandemic on HCM has not been assessed. Methods and Results Age‐adjusted mortality rates based on death certificates from 1999 to 2022 were extracted from the Centers for Disease Control and Prevention Wide‐Ranging Online Data for Epidemiological Research. HCM‐related mortality trends were compared with non‐HCM cardiovascular deaths and all‐cause deaths. Excess HCM‐related deaths were estimated during the 2020 to 2022 COVID‐19 pandemic. From 1999 to 2019, HCM‐related age‐adjusted mortality rates declined progressively, reaching a cumulative 53% (95% CI, 50%–56%) reduction in 2019, exceeding declines in non‐HCM cardiovascular disease (25%) and all‐cause deaths (18%). Declines were evident among all age groups but were most substantial among patients aged 15 to 24 years (62%; 95% CI, 47%–73%) and 25 to 44 years (62% [95% CI, 56%–68%]) but less so in patients aged ≥65 years. During the COVID‐19 pandemic, HCM‐related deaths increased by 31% (95% CI, 23%–40%), exceeding increases in non‐HCM cardiovascular and all‐cause deaths. During the pandemic, 5462 HCM‐related deaths were observed compared with 4770 expected deaths on the basis of the preceding period, resulting in a 692 estimated excess HCM‐related deaths (95% CI, 554–830). Conclusions Based on an analysis of death certificates, the marked decline in HCM‐related deaths of >50% achieved in the US general population during the 2 decades from 1999 to 2019 was substantially reversed (by 29%) during the subsequent 3‐year COVID‐19 pandemic.